THE IMPACT OF THE COVID-19 PANDEMIC ON TOURISM INSURANCE ON THE EXAMPLE OF THE REPUBLIC OF SERBIA - Kovačević Berleković, Bojana; Milić, Dragana; Bošković, Tatjana (Ekonomija - teorija i praksa, 2022)
The aim of the work is to investigate the impact of the pandemic caused by the covid-19 virus on certain forms of insurance in tourism in the market of the Republic of Serbia. The field research was conducted in the period from January to July 2022, and the subject of the research was to investigate the impact of the COVID-19 pandemic on the number and type of insurance plans, the amount of the premium, and the dynamics of insurance in tourism in the Republic of Serbia. The methods used in the work are the inductive-deductive method, the method of analysis and synthesis, the method of observation, the method of comparison, and the statistical method. The research has led us to the conclusion that certain forms of insurance in tourism did not resist the challenge of the pandemic, which confirmed the basic research hypothesis H1. The results of the research indicate that the most dynamic changes relate to tour operator guarantees and travel health insurance, and the importance of the research lies in the fact that it offers practical insights into the matter much needed for insurance researchers, insurers, policyholders, and others looking for solutions to risks associated with the pandemic.